Analisis Kesulitan Siswa pada Pembelajaran Larutan Elektrolit dan Nonelektrolit di Masa Pandemi Covid-19 Menggunakan Model Discovery Learning - Gollu, Angelia Apliana; Muhali, Muhali; Suryati, Suryati; Ahmadi, Ahmadi (Empiricism Journal, 2022)
Penelitian ini bertujuan untuk mengatahui kesulitan siswa memahami materi larutan elektrolit dan nonelektrolit di masa pandemi covid-19 dengan model Discovery learning di SMAN 1 Batu Layar tahun pelajaran 2021/2022. Subjek penelitian adalah seluruh siswa kelas X1 MIPA dengan jumlah 17 orang. Teknik pengumpulan data dilakukan dengan observasi, wawancara, dan soal tes pilihan ganda.Setelah memperoleh data dilakukan analisis dengan menggunakan Mc. Excel dan aplikasi SPSS. Hasil analisis data diperoleh kesulitan angka dan kesulitan dalam memahami rumus kimia zat sebesar 92,652%, selanjutnya kesulitan memahami istilah sebesar 72,06%, dan kesulitan memahami konsep sebesar 69,12%, serta kesulitan di masa pandemi covid-19 sebesar 76,47%. kesulitan siswa dimasa pandemi covid-19 yakni pembelajaran secara daring 82,35%, kesulitan karena koneksi internet 70,59%, dan kesulitan mengerjakan tugas yang menumpuk sebesar 76.47%. menurut hasil rekapitulasi pada model Discovery learning mampu mengingat lebih lama materi sebesar 92,652%, selanjutnya lebih cepat memahami materi sebesar 88,2% dan terakhir lebih aktif mengikuti pembelajaran sebesar 82,35%. Dari hasil analisis ini dapat disimpulkan bahwa siswa mengalami kesulitan terbesar pada materi larutan elektrolit dan nonelektrolit yakni kesulitan angka yang berkaitan dengan hitungan matematis dan menentukan rumus kimia zat dan pada pandemi covid-19 siswa mengalami kesulitan karena pembelajaran dilakukan secara online. Analysis of Students Difficulties in Learning Electrolyte and Non-electrolyte Solutions during the Covid-19 Pandemic Using the Discovery Learning Model Abstract This study aims to find out the difficulties of students understanding the material of electrolyte and nonelectrolyte solutions during the covid-19 pandemic with the Discovery learning model at SMAN 1 Batu Layar for the academic year 2021/2022. The research subjects were all students of class X1 Mathematics and Natural Sciences with a total of 17 people. Data collection techniques were carried out by observation, interviews, and multiple choice test questions. After obtaining the data, analysis was carried out using Mc. Excel and SPSS applications. The results of data analysis obtained that the difficulty of numbers and difficulties in understanding the chemical formula of substances was 92.652%, then the difficulty of understanding terms was 72.06%, and the difficulty of understanding concepts was 69.12%, and the difficulty during the covid-19 pandemic was 76.47%. . students' difficulties during the covid-19 pandemic, namely online learning 82.35%, difficulties due to internet connections 70.59%, and difficulties doing assignments that piled up by 76.47%. according to the recapitulation results, the Discovery learning model is able to remember material longer by 92.652%, then understands material more quickly by 88.2% and finally more actively participates in learning by 82.35%. From the results of this analysis, it can be concluded that students experience the biggest difficulties in electrolyte and nonelectrolyte solution materials, namely the difficulty of numbers related to mathematical calculations and determining chemical formulas of substances and in the covid-19 pandemic students have difficulty because learning is done online.